Virus respiratorios detectados a través de biología molecular en niños hospitalizados por Infección respiratoria aguda en tiempos de SARS-CoV-2/COVID-19 - Isabel Ruiz-Ponce de León (Asociación Colombiana de Infectología, 2021)
Introduction: viral acute respiratory infections have been considered of the main causes of mortality and morbidity in pediatrics, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has become an important problem for global public health for its high transmissibility. The objective of the study is to describe the behavior of respiratory viruses detected by RT-PCR in children hospitalized for acute respiratory infection (ARI) in times of SARS-CoV-2 / COVID19 in pediatric care center in Cali Colombia Methodology: observational with a retrospective cross-sectional study. 113 patients older than 28 days and under 18 years in March to November 2020, hospita-lized with a confirmed diagnosis of ARI and Real Time Polymerase Chain Reaction (RT-PCR) positive for respiratory viruses. Results: Predominance of gender male 64.6%. 74.3% with a diagnosis of low ARI, main symptoms presented were cough 92% and fever 74.3%, SARS-CoV-2 identified 53%, Human Rhinovirus / Enterovirus 27.41% and Respiratory Syncytial Virus 15%. 34.5% of the patients required an intensive care unit with mechanical ventilation requirement 15.9%Conclusions: infection by SARS-CoV-2 was more common in hospitalized patients in both general wards as in the pediatric intensive care unit.